Influence of dietary carbohydrate intake on the free testosterone: cortisol ratio responses to short-term intensive exercise training - Lane, A. R.; Duke, J. W.; Hackney, A. C. (European Journal of Applied Physiology, 2010)
This study examined the effect of dietary carbohydrate (CHO) consumption on the free testosterone to cortisol (fTC) ratio during a short-term intense micro-cycle of exercise training. The fTC ratio is a proposed biomarker for overreaching-overtraining (i.e., training stress or imbalance) in athletes. The ratio was studied in two groups, control-CHO (~60% of daily intake, n = 12) and low-CHO (~30% of daily intake, n = 8), of male subjects who performed three consecutive days of intensive training (~70-75% maximal oxygen consumption, 60 min per day) with a dietary intervention (on the day before and during training). Resting, pre-exercise blood samples were collected under standardized-controlled conditions before each day of training (Pre 1, 2, 3) and on a fourth day after the micro-cycle (Rest). Bloods were analyzed for free testosterone and cortisol via radioimmunoassay procedures. Subjects performed no additional physical activity other than prescribed training. Statistical analysis (ANCOVA) revealed the fTC ratio decreased significantly (p < 0.01) from pre-study resting measurement (Pre 1) to the final post-study resting measurement (Rest) in the low-CHO group (-43%), but no change occurred (p > 0.05) in the control-CHO group (-3%). Findings suggest if the fTC ratio is utilized as a marker of training stress or imbalance it is necessary for a moderately high diet of CHO to be consumed to maintain validity of any observed changes in the ratio value.